Nerd Ecology - Anthony Lioi (Bloomsbury Academic, 2016)
Explores nerd culture's engagement with environmental issues, from Star Trek and Lord of the Rings, to Marvel's X-Men and Joss Whedon's Buffy the Vampire Slayer.
English